Apakah Technostress Berpeluang Memicu Burnout? Studi pada Guru Honorer Usia Dewasa Madya - Cherenita Fonda Patricia; Doddy Hendro Wibowo (Jurnal Psikologi Perseptual)
Honorary teachers are expected to adapt to hone their knowledge and skills in the use of technology, but not all honorary teachers are able to use of technology in schools especially in the middle age range. This study aims to answer the relationship between technostress and burnout tendencies in middle-aged honorary teachers. Researchers used quota sampling technique with a total of 70 participants. The data analysis method uses Pearson's product moment correlation. There are two scales used in this study, namely the technostress scale and the burnout scale. The results showed a correlation of r = 0.534 with p = 0.000 (p 0.01), which means there is a significant positive relationship between technostress and burnout in middle-aged honorary teachers. This means that the higher the level of technostress, the higher the level of burnout. Conversely, the lower the level of technostress, the lower the level of burnout. The results of this study can be a reference for middle-aged honorary teachers to be more adaptive to the use of technology by having the willingness to learn.